TANGGAP STUNTING MELALUI KEGIATAN PENDAMPINGAN PEMBUATAN MAKANAN BERGIZI KEPADA ORANG TUA DI DESA CANGKRING, KABUPATEN LAMONGAN - Puspita, Irma Maya; Marcella Zein Afrilyana; Siti Sholikha (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is caused by multi-dimensional factors and not only caused by malnutrition which is experienced by pregnant women and children under five. The most decisive intervention to reduce the prevalence of stunting can be started in the first 1,000 days of life (HPK) of children under five. Lamongan is one of 5 regencies in East Java which has a high stunting rate of 27.5%. Community service activities are carried out to help reduce stunting rates in Lamongan, especially Cangkring Village, this activity is carried out in line with the Lamongan government program, namely providing counseling to parents who have toddlers, as well as parents who will have children. The number of participants who took part in this activity was 28 people. This activity began with counseling on the stunting response by paying attention to toddler nutrition and pregnant women's nutrition followed by demonstrations of making stunting-free food made from catfish which is easily available in Lamongan. Community Service activities carried out at the Cangkring Village Hall resulted in increased public knowledge about stunting and nutritious food as seen from the results of the questionnaires before and after counseling. Increasing public knowledge about stunting and how to prevent stunting in children is expected to be able to minimize the potential for stunting in children in Indonesia, especially in Cangkring Village, Bluluk District, Lamongan.